A reconfigurable ultra wide band (UWB) compact tree-design antenna system - Muzammil, Jusoh; Mohd Faizal, Jamlos, Dr.; Muhammad Ramlee, Kamarudin; Mohd Fareq, Abd. Malek, Dr.; Muhamad Asmi, Romli; Zahari, Awang Ahmad; Mahathir, H. Mat (The Electromagnetics Academy, 2013)
Link to publisher's homepage at http://www.emacademy.org/